التَّقَابل الدَّلَالِيّ في القرآن الكريم سُورَة يونس--(نموذجًا) (Comprehensive Journal of Science, 2026)
This research addresses the phenomenon of semantic opposition in the Qur’an, taking Surah Yunus (peace be upon him) as a model. Semantic opposition is considered one of the most prominent rhetorical and semantic features in the Qur’anic text, as it contributes to highlighting meaning and guiding the reader toward various doctrinal and ethical concepts. The study adopts a descriptive-analytical approach, structured into two main sections preceded by an introduction and followed by a conclusion that presents the most significant findings. Among these findings is that semantic opposition permeates most of the verses of Surah Yunus. Despite the abundance and recurrence of oppositions in several contexts, each instance appears in a distinct form shaped by the Qur’anic context, which requires establishing the paired opposites in creed, thought, and sentiment